Determination of total alkaloid content in 70% and 96% ethanol extracts of red seaweed (Eucheuma spinosum) obtained by maceration using UV-Vis spect - Sindi Arlin Natasya; Dwi Kurnia Putri; Rose Intan Perma Sari; Samwilson Slamet; Putri Mulia; Nurfitriyana Nurfitriyana (Indonesian Journal of Health Science, 2026)
Red seaweed (Eucheuma spinosum) is one of the marine biological resources containing various secondary metabolites, including alkaloids which possess important biological activities. Differences in ethanol concentration may affect the amount of alkaloid compounds extracted. This study aimed to compare the alkaloid content of 70% ethanol extract and 96% ethanol extract of red seaweed (Eucheuma spinosum) obtained by maceration using the UV-Visible spectrophotometric method. This research was conducted experimentally in the laboratory using the maceration extraction method with 70% and 96% ethanol solvents. Qualitative identification of alkaloids was performed using Mayer, Wagner, and Dragendorff reagents, while quantitative determination was carried out using UV-Visible spectrophotometry with caffeine as the standard at a maximum wavelength of 275 nm. Phytochemical screening results indicated that both 70% and 96% ethanol extracts were positive for alkaloid compounds. The extraction yield of the 70% ethanol extract was 22.945%, whereas the 96% ethanol extract yielded 12.45%. The results of alkaloid determination showed that the 70% ethanol extract contained an average alkaloid level of 5.5 ± 0.22 mg QCE/g, while the 96% ethanol extract contained 5.3 ± 0.10 mg QCE/g. It can be concluded that the 70% ethanol extract produced a slightly higher alkaloid content than the 96% ethanol extract of red seaweed (Eucheuma spinosum).